Evaluasi Implementasi Kurikulum Cambridge dengan Model CIPP - Suri, Sufyan; Sholeh, Muhamad; Roesminingsih, Erny (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research aims to evaluate the implementation of the Cambridge curriculum using the CIPP evaluation model with four evaluation components, namely context, input, process, and product. The research was carried out at Al Azhar 13 Islamic Junior High School, Surabaya. This research is evaluation research using a qualitative approach. The data analysis technique used is the Miles, Huberman & Saldana’s technique, namely data condensation, display, and verification. The results of the research show that Al Azhar 13 Islamic Junior High School carried out a good context evaluation, one of which was the program background, objectives, and environmental factors and needs. Input evaluation was also carried out well, demonstrated by the existence of resource factors that support curriculum implementation, namely human resources and infrastructure. The process evaluation was carried out well and went through several process stages from planning to evaluation. Product evaluation was also carried out well, demonstrated by the results and impact of curriculum implementation. The conclusion given is in the form of a recommendation for Al Azhar 13 Islamic Junior High School Surabaya to continue implementing the Cambridge curriculum to increase international insight and the quality of education.